Optimizing Machine Translation to Overcome Mechanical Engineering Vocational Education Students Difficulties in Academic Writing - Trisya Avianka; Siti Drivoka Sulistyaningrum (Script Journal: Journal of Linguistics and English Teaching, 2021)
Background: Machine translation has been proved to be a favourable style to execute. However, some research evidence difficulties indicates that its focus is on students' difficulties in academic writing, not on how to overcome them by using machine translation. As a result, this research aims to determine how machine translation might be optimized to help mechanical engineering vocational education students with academic writing difficulties. Methodology: The data was collected from 27 second-semester mechanical engineering vocational education students currently enrolled in an English college course at one of the Universities in Jakarta. Questionnaires online were used to obtain the data, which was analyzed and interpreted descriptively. Questionnaire 1 is used to determine whether or not the subject utilized machine translation and, if so, what type of machine translation they used most frequently. Question 2 was split into two sections. PART A was modified from Xiao & Chen (2015), who described students' challenges with academic writing. It comprises 12 items that were delivered to 27 students via Google Form. Meanwhile, the findings of Lee (2020) have been adapted into PART B. Findings: The result of this study revealed that 27 students of mechanical engineering vocational education in one of the Universities in Jakarta encountered several academic writing difficulties such as grammar (construct grammatically correct sentences, the use of appropriate tenses), expressions (discourse markers, part of speech), and vocabulary (proper vocabulary choices and finding synonyms). Grammar problems are the most challenging, followed by vocabulary and phrases. The optimization of machine translation was also discovered to be the most effective way of overcoming vocabulary issues followed by grammar and expression. Conclusion: Academic writing issues emerge in the classroom. According to the findings, the most difficulties students encountered fell into the grammar aspect. On the other hand, the students considered that machine translation would be the most helpful in overcoming their vocabulary challenges. Although machine translation helps deal with academic writing difficulties like developing vocabulary skills, increasing knowledge of grammar rules in context, and finding more authentic expression, teachers should also guide them in writing academically. Keywords: optimizing machine translation; academic writing difficulties; grammar; vocabulary; expressions.